DESKRIPSI KESALAHAN SISWA KELAS VIII SMPN 33 MAKASSAR DALAM MENYELESAIKAN MASALAH SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) BERDASARKAN TAHAPAN NEWMAN - Haryanti Dahlan; Sitti Rahmah Tahir; Usman Mulbar (JSSHA ADPERTISI JOURNAL, 2021)
The purpose of this research was to describe the errors of the eighth grade students of SMP Negeri 33 Makassar in solving the two-variable linear equation system problem based on the Newman stage. This type of research was a descriptive research with a qualitative approach. The data collection in this research was conducted by using the assignment and interview methods. The research subjects were taken by 4 people from students of class VIII-F, each consisting of 2 students who had the most errors and 2 students who had the least errors. Each research subject was interviewed based on the results of his work on two-variable system of linear equations. Testing the validity of the data by using the time triangulation technique. From the research results, it could be concluded that in the first and second assignments, all subjects had no errors at the reading and comprehension error stages of the questions. There was one subject who got a transformation error, namely the GAG (male) subject and the other subject did not get an error in the part of changing the problem into the correct mathematical model. As many as two subjects got errors in process skills, namely HKR (female) subjects and GAG (male) subjects and other subjects did not get errors in this section. There were two subjects who got errors in the error because the subject was wrong in the process skills, so the subject got an error at the encoding error stage